Khemiri, Khaoula - (:unkn) unknown (My University, 2026)
Khaoula Khemiri is a PhD in Hydraulic Engineering in the National Engineering School of Tunis (ENIT) and the National Research Institute of Rural Engineering, Water and Forests (INRGREF), holds a master degree in Hydraulic and Environmental Modeling and a degree of Hydro-Meteorological engineer from ENIT. Her research fields of interest are sediment transport and water erosion assessment, remote sensing and Hydrological modeling.